Processamento do queijo de manteiga artesanal maturado - Fernandes, Dayse Ariane Soares Medeiros (Universidade Federal Rural do Semi-Árido, 2021)
During the cheese ripening, physical changes and substances occur, which generate substances needed to change its flavor and aroma. As a result, this study aimed to evaluate the microbiological quality and physicochemical parameters of artisanal butter cheese during the period from zero to 60 days of the maturation period. Cheeses were taken on days 0, 15, 30, 45 and 60 analyzed the microbiological quality (count of mesophilic aerobic bacteria, Staphylococci coagulase positive, Salmonella spp., Coliforms at 36ºC, Escherichia coli, molds and yeasts) and physicochemical ( acidity, pH, moisture, protein and fat content). Analyzes regarding the colorimetric profile and texture parameters of hardness, adhesiveness, elasticity, cohesiveness, gummyness, chewiness and resilience were also evaluated. A reduction in microbiological contamination was observed for Staphylococcus coagulase positive and coliform microorganisms at 36 °C. Escherichia coli and Salmonella spp were not found in any of the forced times. However, there was an increase in the count of mesophilic aerobic bacteria, molds and yeasts. Regarding the acidity and pH parameters, there were no differences. The moisture content had an average value of 15.33%, not complying with the legislation. The maximum value found for the fat parameter was 36.24%, acceptable value by law. Regarding the amount of protein in the sample, there was no significant difference, except on day 60, when there was an increase in this parameter. As a tendency to yellow coloration. Regarding the texture parameters, most do not show any difference during the evaluation. Despite the variations found in microbiological and physicochemical parameters, it can be said that maturation helps in the microbiological and physicochemical quality of artisanal butter cheese
Keywords: Queijo de manteiga; Queijo artesanal; Qualidade microbiológica; Butter cheese; Artisanal cheese; Microbiological quality; CIENCIAS AGRARIAS::ZOOTECNIA